Inconsistency-Adaptive Logics - Batens, Diderik (Logic at Work. Essays Dedicated to the Memory of Helena Rasiowa, 1999)
After a general description of adaptive logics and their intended applications, I study the proof theory and semantics of two closely related predicative inconsistency-adaptive logics, ACLuN1 and ACLuN2. To this end, I first describe their monotonic basis: the paraconsistent logic CLuN obtained by dropping the consistency requirement from classical logic. The propositional fragments of these inconsistency-adaptive logics have been studied elsewhere. The predicative versions involve several interesting difficulties that lead to new results.